A Semiotic Analysis of Nationalism in Bakatsir's 'Biladaka Ya Hatta' through Riffaterre's Theory - Fikri, Maulana Muhammad; Fitriani, Laily; Hasaniyah, Nur; Ayvaz, Harun (Langkawi: Journal of The Association for Arabic and English, 2024)
This study analyzes Ali Ahmad Bakatsir’s Biladaka Ya Hatta using Michael Riffaterre’s semiotic theory to explore themes of nationalism during Indonesia’s independence struggle. The poem, rich in metaphor, enjambment, and symbolic language, portrays both the spiritual and political dimensions of Indonesia’s fight for freedom. Through Riffaterre’s heuristic and hermeneutic reading methods, the research uncovers how the poem's surface meanings evolve into deeper interpretations. Bakatsir’s strategic use of language highlight’s themes of patriotism and unity, with vivid imagery such as "heaven and lake" evoking Indonesia's natural beauty, and "the blowing storm of disaster" emphasizing the nation's enduring hardships. The poem’s intertextuality bridges classical Arabic literary traditions with Indonesia’s contemporary socio-political context, linking the fight for national identity to broader global struggles, including solidarity with Palestine. This fusion of cultural influences underlines the poem’s ongoing relevance in shaping national consciousness. Through Riffaterre’s semiotic framework, the study reveals how Biladaka Ya Hatta transcends mere patriotic sentiment, offering a complex, multilayered narrative of resistance and collective memory. The poem’s linguistic richness, interwoven with psychological and cultural significance, underscores its importance in both personal and national identity formation. The research demonstrates the enduring relevance of semiotic analysis in literary studies and its adaptability in exploring works that engage with themes of nationalism and social transformation.